(6-7i)/(-2-8i)=0

Simple and best practice solution for (6-7i)/(-2-8i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6-7i)/(-2-8i)=0 equation:



(6-7i)/(-2-8i)=0
Domain of the equation: (-2-8i)!=0
We move all terms containing i to the left, all other terms to the right
-8i!=2
i!=2/-8
i!=-1/4
i∈R
We add all the numbers together, and all the variables
(-7i+6)/(-8i-2)=0
We multiply all the terms by the denominator
(-7i+6)=0
We get rid of parentheses
-7i+6=0
We move all terms containing i to the left, all other terms to the right
-7i=-6
i=-6/-7
i=6/7

See similar equations:

| 12x^2-9=33x | | 5y+12-2y=-7-78 | | f(4)=5(4)-2 | | 3/2x-13=5x+1 | | (x+3)^2-1=35 | | -12k–-3k–14k+20k=-6 | | 10(4)^2x-1-5=7 | | 2(96+2w)=80-3w | | 8p–6p=12 | | (x+3)^2​−1=35 | | x+1,5=6 | | 43h+2=17+5 | | x-9=3x+-7 | | 1/4n=60 | | 5n-3=38 | | x+8=3x-3 | | -3h=-5-(1/2) | | c17=3 | | 12=5y+6 | | 7x+6(-3x+3)=-48 | | -2(3n-5)+5n=(6(n-3) | | -5b+14=-4b-9 | | 3(2z+1)=6z-2)+14 | | 3j=4/5 | | 12z-9z+-z-8z-10z=16 | | 23=5(x+5)-7x | | −2/3x+37=12 | | 5x+5=1x+9 | | 12z–9z+-z–8z–10z=16 | | 7x/2=20 | | 6x=x^2-4x+11 | | 5z-z-3z=3 |

Equations solver categories